1977
DOI: 10.1007/bf01223266
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, seasonal and geographical patterns of juvenile-onset insulin-dependent diabetes mellitus in Denmark

Abstract: The incidence, sex, seasonal and geographical patterns of juvenile-onset insulin-dependent diabetes mellitus (j.i.d.m.) were studied retrospectively on one third of the Danish population 1970-1974. The j.i.d.m. incidence remained fairly constant during the study period, the average being 13.2 per 100000 per year. The total number of boys exceeded the number of girls by 27%. A marked peak of incidence was found at 12-14 years, earlier for females than for males. A seasonal variation in onset (diagnosis) of j.i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
70
9
2

Year Published

1980
1980
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 9 publications
18
70
9
2
Order By: Relevance
“…This finding is in contrast with the findings of other studies were childhood peaks were reported [2,9,10]. However, our number is too small for analysis.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…This finding is in contrast with the findings of other studies were childhood peaks were reported [2,9,10]. However, our number is too small for analysis.…”
Section: Discussioncontrasting
confidence: 97%
“…There was a slight increase in incidence in the 0-19 year age group, but it is lower than that reported from Toronto (9.50 per 100,000) [6], New Zealand (10.4 per 100,000) [7] and much lower than the Finnish findings of 27.3 per 100,000 [8]. The incidence of diabetes mellitus in the age group 0-29 years in Kuwait (22.09 per 100,000) is nearly twice that found in Denmark (13,2 per 100,000) [2]. The majority of new cases of diabetes mellitus in the present study was in the 20-29 year age group, representing 80% of all new cases and accounting for the majority of cases which did not require insulin.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The pattern of seasonality is similar to that reported in many other studies [8,12,14,[31][32][33][34][35] with excess incidence in the local winter. Some studies have not shown this [17,36].…”
supporting
confidence: 76%
“…The higher incidence figure was very similar to that obtained in a much smaller incidence study in Denmark (14 per 100,000), where the ascertainment was virtually 100%. 8 Thus, by taking this incidence rate, the prevalence of type I diabetes at the age of 16 yr is 0.22%. This is very important when we consider the genetic basis of the disease.…”
Section: Prevalence Of Type I Diabetes In Childrenmentioning
confidence: 99%